The safety effect of exchanging car mobility for bicycle mobility. Substituting a small number of short car trips with bicycle trips. - Stipdonk, Henk; Reurings, Martine (My University, 2010)
Die Analyse untersucht den Effekt, den eine Verringerung der Autonutzung zu Gunsten der Fahrradnutzung auf Kurzstrecken hat. Die empirische Basis stellen dabei die Anzahl der im Straßenverkehr verursachten Unfälle sowie die daraus resultierenden ernsthaften Verletzungen dar. Aufgrund geringer empirischer Datenmengen dient diese Studie als erste Annäherung an dieses Thema.

This report describes the analysis of the effect of exchanging passenger car mobility for bicycle mobility on the number of fatalities and serious road injuries in the Netherlands. A precise calculation of this effect was not possible due to a lack of information, instead the report gives a first and rough approximation of the safety effect.
Keywords: Individualverkehr; Fahrradverkehr; Untersuchung; Bewertung; Verkehrssicherheit; Verkehrsunfall; Unfallverhütung; Verkehrsverhalten; Fahrradnutzung; Unfallanalyse